The Use of the Auto Base Accounts on Twitter as A Media for Sharing Opinions: Case Study of @collegemenfess Account - Risma Hasna Dwiwina; Kinkin Yuliaty Subarsa Putri (Universitas Multimedia Nusantara, 2021)
Almost everyone in the world currently uses social media. Social media can make it easier for humans to communicate, interact, discuss, and exchange opinions with its various types and functions. One of the most widely used social media is Twitter. With its features, Twitter makes it easy for users to interact and communicate. Twitter is now not only used by government and celebrity accounts but also auto base accounts. The auto base account has also caught the attention of Twitter users because it allows anonymous messaging. The account can be a medium for Twitter users to channel the same likes in a community and a medium for discussing and sharing opinions. One of the auto base accounts on Twitter that is widely used as a medium for discussing and sharing opinions is the @collegemenfess account. This account is intended for students, and can be used to share opinions with each other. The phenomenon of auto base and its use has attracted researchers to find out how to use an auto base as a medium for sharing opinions. This study uses a qualitative descriptive method with content analysis on the @collegemenfess auto base account. The analysis results show that @collegemenfess auto base users use this account as a medium for sharing opinions. The researcher concludes that sharing opinions is done through the menfess sent, as well as through comments related to an issue that is being discussed on the @collegemenfess account. Keywords: Auto Base, menfess, Social media, Twitter, Opinion.